Effects of flushing on electro-discharge machined surface - Shamsul Shahril, Mat Yunus (2008)
Electrode discharge machining is the process for shaping hard metal and forming deep by arc erosion in all kind of electro conductive material. The objective of this research is to study effect of flushing parameter of EDM of tungsten carbide on the machining characteristics. The effectiveness of the EDM process with tungsten carbide is evaluated in term of surface roughness, and microstructure of the workpiece also to optimize the machining parameter of machining tungsten carbide using EDM machine. Experiment on tungsten carbide material was carried out using difference pressure flushing machining parameter with copper tungsten electrode. Base on the flushing pressure gauge at machined EDM AQ55L the range pressure flushing on this machine EDM is 0.025 to 0.125 Mpa. In this experiment, the jet flushing pressure is used for flow the dielectric into the gap spark between electrode and workpiece. Better machine performance is obtained generally with the electrode as the cathode and the workpiece as the anode. The optimal flushing pressure is found to be at 0.1 MPa. This is the best flushing rate that will be chose in the parameters because it has small surface roughness. There is little variation on the surface roughness of the workpiece, although at 0.1 Mpa the surface finish tends to be better. At 0.05 MPa to 0.1 Mpa, the grain solid debris begins to decrease on the surface at this pressure. Effects from the higher spark formed a large void and the grains bunchy exist in that area also sticks together in the void.